Residents' experiences during a hydrogen sulfide crisis in Carson, California - Arbor J. L. Quist; April Hovav; Alexander D. Silverman; Bhavna Shamasunder; Jill E. Johnston (BMC, 2024)
Abstract Background In early October 2021, thousands of residents in Carson, California began complaining of malodors and headaches. Hydrogen sulfide (H2S), a noxious odorous gas, was measured at concentrations up to 7000 parts per billion (ppb) and remained above California's acute air quality standard of 30 ppb for a month. Intermittent elevations of H2S continued for 3 months. After 2 months of malodor in this environmental justice community, a government agency attributed the H2S to environmental pollution from a warehouse fire. Research has yielded conflicting results on the health effects of H2S exposure at levels that were experienced during this event. This research fills a critical need for understanding how people perceive and experience emergent environmental health events and will help shape future responses. Methods Through a community-academic partnership, we conducted 6 focus groups with 33 participants who resided in the Carson area during the crisis. We sought to understand how this incident affected residents through facilitated discussion on topics including information acquisition, impressions of the emergency response, health symptoms, and ongoing impacts. Results The majority of participants were women (n = 25), identified as Latina/o (n = 19), and rent their homes (n = 21). Participants described difficulty obtaining coherent information about the emergency, which resulted in feelings of abandonment. Most participants felt that local government and healthcare providers downplayed and/or disregarded their concerns despite ongoing odors and health symptoms. Participants described experiencing stress from the odors' unknown health effects and continued fear of future odor incidents. Residents sought to take control of the crisis through information sharing, community networking, and activism. Participants experienced longer term effects from this event, including increased awareness of pollution and reduced trust in local agencies. Discussion This study demonstrates the necessity of clear, comprehensive, and prompt responses by relevant decisionmakers to chemical emergencies to appropriately address residents' fears, curb the spread of misinformation, and minimize adverse health effects. Participant responses also point to the benefit of supporting horizontal community networks for improved information sharing. By engaging directly with community members, researchers and disaster responders can better understand the various and complex impacts of chemical disasters and can improve response.